Methods and Means of Developing Professional Competence Qualities of Teachers in Training Using Uzbek Folk Pedagogy - Nabijonovna, Saidmuradova Sitora (ANTIS PUBLISHER, 2024)
In this state, the importance of using Uzbek national pedagogy and education of professional-competent qualities of pedagogues and raising qualifications, self-image of education of professional-moral qualities of pedagogues, na osno natsionalnyx traditional, customs and tradition of the Uzbek nation